Pt-doped single-walled CNT as a superior media for evaluating the operation status of insulation devices: A first-principle study - Song Xiao; Jun Zhang; Xiaoxing Zhang; Hao Cui (AIP Advances, 2018)
Detecting SF6 decomposed species by chemical gas sensors has been accepted as a workable method to estimate the operation status of insulation devices in electrical engineering. Functioned by transition metals, carbon nanotubes (CNTs) would be provided with enhanced sensitivity and response towards gas molecules due to the high catalytic activity of metals for gas interaction. This has been the focus of attention in recent years. In this paper, the adsorption of three SF6 decomposed components (SO2F2, SO2 and H2S) onto Pt-doped CNT were simulated based on density function theory method. Results indicated that Pt-CNT has the best sensitivity to H2S causing remarkably conductivity change accordingly, followed by SO2, and the last one comes to SO2F2. Pt dopant exerts great impacts on adsorption of gas molecules onto CNT surface through providing active adsorption sites for CNT support. Our calculation results would be meaningful to suggest advanced sensing materials being applied in the field of electrical engineering.